2021
DOI: 10.3389/fcell.2021.637781
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Glucose Metabolism in Male Mice Offspring Conceived by in vitro Fertilization and Frozen-Thawed Embryo Transfer

Abstract: Frozen and thawed embryo transfer (FET) is currently widely applied in routine assisted reproductive technology (ART) procedure. It is of great necessity to assess the safety of FET and investigate the long-term effect including glucose metabolism on FET-conceived offspring. The mouse model is a highly efficient method to figure out the relationship between the process of FET and offspring health. In this study, we obtained mouse offspring of natural conception (NC), in vitro fertilization (IVF), and FET. Gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 49 publications
1
18
0
1
Order By: Relevance
“…In agreement with our findings, several studies described non-polar and semi-polar metabolism alteration after embryonic manipulation [ 10 , 20 , 21 , 22 , 23 , 24 , 25 ]. Globally, semi-polar metabolites were up-accumulated while non-polar metabolites were down-accumulated in MOVET animals compared to NC animals, suggesting a metabolic adaptation strategy [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Related to this, Feuer et al observed that conception by IVF reduces growth, impairs glucose tolerance and impacts the serum and liver metabolome, affecting a wide range of compounds such as carbohydrates, amino acids, and, especially, lipids [ 10 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with our findings, several studies described non-polar and semi-polar metabolism alteration after embryonic manipulation [ 10 , 20 , 21 , 22 , 23 , 24 , 25 ]. Globally, semi-polar metabolites were up-accumulated while non-polar metabolites were down-accumulated in MOVET animals compared to NC animals, suggesting a metabolic adaptation strategy [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Related to this, Feuer et al observed that conception by IVF reduces growth, impairs glucose tolerance and impacts the serum and liver metabolome, affecting a wide range of compounds such as carbohydrates, amino acids, and, especially, lipids [ 10 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Investigating the effects of ART in fertile model species circumvents issues raised by underlying infertility and avoided other confounding factors, especially those regarding birth weight and growth trajectories, metabolic health, cardiovascular troubles and epigenetic alterations [ 15 ]. The mechanism underlying the alterations in offspring conceived with ARTs are not entirely clear, but epigenetic changes are a well-excepted contributor [ 2 , 5 , 14 , 15 , 16 , 17 ]. Here, we exploit our rabbit ARTs model to conduct a hepatic DNA methylation association study with metabolomics and proteomics in the F3 generation for embryonic exposure (multiple ovulation, vitrification and embryo transfer) conceived offspring, as well as assess the potential health implications.…”
Section: Introductionmentioning
confidence: 99%
“…Two-cell embryos in IVF-ET and IVF-FET groups were obtained by standard B6D2F1 × B6D2F1 IVF. The IVF, embryo transfer, embryo frozen, and thawed procedures have been described previously ( Qin et al 2021 ). The offspring were weaned and separated by sex until postnatal day 20.…”
Section: Methodsmentioning
confidence: 99%
“…These changes are characterized by insulin resistance and alterations of the function of proteins related to glucose metabolism. Therefore, these changes could be a risk factor for metabolic diseases as type 2 diabetes [ 66 , 67 , 68 ].…”
Section: Molecular Alterations In Cryopreserved Embryosmentioning
confidence: 99%